1989
DOI: 10.1111/j.1365-2265.1989.tb02235.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass in Hirsute Women With Androgen Excess

Abstract: The spinal and femoral bone mass of 32 hirsute women with oligomenorrhoea and androgen excess was measured using dual photon absorptiometry and compared with the bone mass of 32 control women with regular menstrual cycles. Despite significantly lower oestradiol levels in the hirsute population there was no significant difference in the bone mass. Furthermore there was no significant difference in bone mass in five hirsute women with undetectable levels of oestradiol. It is concluded that androgen excess can ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Estrogen deficiency drives menopausal bone loss and can be used therapeutically to prevent such loss (1,2). Estrogen deficiency also plays a primary role in the bone loss associated with menstrual disturbances in young women (3)(4)(5)(6), although there may be circumstances where the detrimental skeletal effects of estrogen deficiency can be avoided (8)(9)(10)(11). In the healthy, normally cycling women recruited for the current study, after 3-5 yr of follow-up, there was evidence of premenopausal bone loss only from the hip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen deficiency drives menopausal bone loss and can be used therapeutically to prevent such loss (1,2). Estrogen deficiency also plays a primary role in the bone loss associated with menstrual disturbances in young women (3)(4)(5)(6), although there may be circumstances where the detrimental skeletal effects of estrogen deficiency can be avoided (8)(9)(10)(11). In the healthy, normally cycling women recruited for the current study, after 3-5 yr of follow-up, there was evidence of premenopausal bone loss only from the hip.…”
Section: Discussionmentioning
confidence: 99%
“…Perimenopausal women with higher testosterone concentrations have slower rates of bone loss than those with lower concentrations, independent of their estrogen status (7). Premenopausal women with androgen excess have higher than normal bone mass with or without (8,11) normal menstrual cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the nonaromatizable androgen 5a-dihydrotestosterone has been shown to stimulate bone growth in osteopenic ovariectomized rats (24). In pre-and postmenopausal women, endogenous androgen levels correlate with BMD (25,26). Furthermore, a study comparing estrogen to a synthetic androgen in postmenopausal osteoporotic women showed that both steroids were equally effective in reducing bone resorption (27).…”
Section: Introductionmentioning
confidence: 99%
“…Further, testosterone deficiency has been implicated as a causative factor in female osteoporosis with the decline of adrenal androgens associated with aging [Gasperino, 1995;Wild et al, 1987]. Androgens have been shown to maintain normal bone mass despite undetectable levels of estradiol [Dixon et al, 1989], and androgen therapy in postmenopausal women has been shown to prevent bone loss [Need et al, 1989]. Androgen receptors have been identified in the nucleus and cytosol of osteoblasts [Nakano et al, 1994;Orwoll et al, 1991].…”
mentioning
confidence: 99%